Treatment of Comorbid Alcohol Dependence and Anxiety Disorder: Review of the Scientific Evidence and Recommendations for Treatment - Gimeno, Carmen; Dorado, Marisa Luisa; Roncero, Carlos; Szerman, Nestor; Vega, Pablo; Balanzá-Martínez, Vicent; Alvarez, F. Javier (Frontiers in Psychiatry, 2017)
Patients with alcohol use disorders (AUDs) have a high prevalence of anxiety disorders (AnxDs). ‘Co-occurring disorders’ refers to the coexistence of an AUD and/or drug related disorders with another non-addictive psychiatric disorder. The aim of this study was to assess the effectiveness of psychopharmacological treatments and psychotherapy in patients with AUD and AnxD, and to propose recommendations for the treatment of patients with co-morbid AnxDs and AUDs. Randomized clinical trials, meta-analyses, and clinical guidelines were retrieved from PubMed, Embase and Cochrane databases. Paroxetine was found to be effective in social anxiety patients with alcohol dependence. Selective serotonin re-uptake inhibitors (SSRIs), especially sertraline, showed effective results in post-traumatic stress disorder and in co-morbid AnxD-AUD. However, SSRIs should be used with caution when patients are actively drinking because they may increase alcohol consumption. Buspirone, gabapentin and pregabalin were found to be effective in co-morbid AnxD-AUD. The treatment of dual anxiety disorders should start as early as possible. Since AUDs and AnxDs can reinforce each other, treatments targeting both pathologies can be effective. Women suffer from higher levels of stress and AnxDs than men, and they are also more vulnerable to maintaining alcohol consumption levels. Further research is needed in this co-morbid patient population, including the study of different types of patients and gender perspectives.